Pituitary Adenylate Cyclase-Activating Polypeptide Protects Glomerular Podocytes from Inflammatory Injuries - Kenichi Sakamoto; Kyoko Kuno; Minoru Takemoto; Peng He; Takahiro Ishikawa; Shunichiro Onishi; Ryoichi Ishibashi; Emiko Okabe; Mayumi Shoji; Akiko Hattori; Masaya Yamaga; Kazuki Kobayashi; et al. (Journal of Diabetes Research)
Diabetic nephropathy (DN) is a leading cause of end-stage kidney disease; however, there are few treatment options. Inflammation plays a crucial role in the initiation and/or progression of DN. Pituitary adenylate cyclase-activating polypeptide (PACAP) is a neuropeptide, which was originally isolated from the ovine hypothalamus and reportedly has diverse biological functions. It has been reported that PACAP has renoprotective effects in different models of kidney pathology. However, the specific cell types within the kidney that are protected by PACAP have not yet been reported. In this study, we localized VPAC1, one of the PACAP receptors, to glomerular podocytes, which also reportedly has crucial roles not only in glomerular physiology but also in pathology. PACAP was effective in the downregulation of proinflammatory cytokines, such as monocyte chemoattractant protein-1 (MCP-1) and interleukin-6, which had been induced by the activation of toll-like receptor (TLR) with lipopolysaccharide. PACAP also had downregulated the expression of MCP-1 through the protein kinase A signaling pathway; this led to the attenuation of the activation of extracellular signal-regulated kinase and nuclear factor-kappa B signaling. Our results suggested that PACAP could be a possible treatment option for DN through the use of anti-inflammation effects on glomerular podocytes.